Effect of sodium salts of branched chain volatile fatty acids on extra cellular ammonia utilization and protein production in vitro - MISRA, A K; THAKUR, S S (The Indian Journal of Animal Sciences, 2012)
Effects of Na salts of branched chain volatile fatty acids (isobutyric, isovaleratic and 2–methyl butyric) addition (@ 0.75 and 1.50%) in the substrates containing wheat straw, green fodder and concentrate mixture (40:40:20) and varying in protein content (8, 10 and 12%) and nitrogen sources (with and without urea) on dry matter digestion, utilization of extra cellular ammonia and protein production in the in vitro medium were investigated. Inclusion of BCFA in the substrate @ 0.75 and 1.50%, increased (P